Analisis Perkembangan Berpikir Kritis Siswa dalam Pembelajaran Matematika Perspektif Studi Longitudinal - Suwarma, Dina Mayadiana; Hersiyati Palayukan; Nasruddin; Sitti Rahmayani; Syarifuddin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research explores the development of students' critical thinking in mathematics learning through a longitudinal study approach. With a focus on problem solving, creative thinking, and conceptual understanding, this study aims to understand how students develop critical thinking skills over time. A longitudinal research method was used with 100 students from two secondary schools in Medan city as participants. Results showed significant improvements in students' critical thinking scores from the beginning to the end of the semester, with teacher training interventions and differences between schools making significant contributions. The implication of this study is the importance of innovative learning approaches and support for teachers in improving students' critical thinking skills in the context of mathematics learning